Critical evaluation of two commercial biocontrol agents for their efficacy against B. cinerea under in vitro and in vivo conditions in relation to different abiotic factors - Tut, Gurkan; Magan, Naresh; Brain, Philp; Xu, Xiangming (MDPI, 2021)
The study evaluated the dose–response relationship of two commercial microbial biocontrol agents, Bacillus subtilis and Gliocladium catenulatum, against Botrytis cinerea both in vitro and in vivo. Inoculum doses, formulation, temperature and foliar leaf part all affected the control achieved by the two BCAs. In vitro competition assays on modified PDA plates tested a range of BCA doses (log10 3–10 CFUs or spores/droplet) at 4, 10 and 20 °C on the development of B. cinerea colonies. The dose–response relationship was influenced by both the BCA formulation and temperature. In vivo studies on lettuce plants in semi-commercial greenhouses examined the BCA dose (log10 5–9 CFUs or spores/mL) for controlling B. cinerea with a high inoculum (log10 6 spores/mL). Leaf disc assays showed that the dose–response relationship was influenced by the leaf parts sampled. These results suggest that the dose–response relationship between a BCA and specific pathogen will be significantly influenced by environmental conditions, formulation and plant phyllosplane tissue.
Keywords: commercial biocontrol agents; formulation; temperature; Botrytis cinerea; Bacillus subtilis; Gliocladium catenulatum; biocontrol; dose–response; spatial effects